Heart rhythm during episodes of collapse in boxers with frequent or complex ventricular ectopy. (4th February 2020) - Domingues, M.; Brookes, V. J.; Oliveira, P.; Mavropoulou, A.; Willis, R.
Abstract : Objectives: To describe heart rhythm during collapse events in boxer dogs using ambulatory electrocardiogram and determine the predictive value of frequent or complex ventricular ectopy for collapse associated with ventricular tachycardia. Materials and Methods: A total of 659 ambulatory electrocardiogram recordings from 429 boxer dogs were identified from a database in the UK. Summary statistics described the frequency and complexity of ventricular ectopy during all recordings, recordings in which collapse occurred and associated boxer demographics. Positive predictive values were calculated to investigate whether frequent ventricular ectopy was useful to predict heart rhythm during episodes of collapse. Results: Of the 659 ambulatory electrocardiogram recordings, 250 recordings showed <50 single ventricular beats (Group 1), and frequent (≥50) or complex ventricular ectopy were observed in 409 recordings (Group 2). A total of 90 collapse events were observed in 72 ambulatory electrocardiograms from 68 dogs, comprising 30 dogs in Group 1 and 38 dogs in Group 2. In both groups, sinus rhythm was the most frequent collapse rhythm, followed by neurally mediated collapse and then ventricular tachycardia. The proportion of dogs that displayed ventricular tachycardia‐associated episodic collapse given that they had frequent (≥50) or complex ventricular ectopy in the study population was 0.11 [95% confidence interval = 0.01 to 0.21]. Clinical Significance: These results challenge the preconception that UK boxer dogs with collapse will have ventricular tachycardia and, consequently, the authors recommend definitive diagnosis of the cause of episodic collapse to guide selection of therapeutic drugs.